Technological impact on disaster management information system - Islam, Humayun Kadir; Pathan, Al-Sakib Khan (2004)
The impact of extreme events across the globe is extraordinary, continues to handicap the advancement of the struggling developing societies and threaten most industrialized countries in the world. ICT has widely been used for efficient disaster management; but only to a limited extent though, there is a tremendous potential for increasing efficiency and effectiveness in coping with a disaster. Response to the particular situation and proper recovery are among the main focuses of an efficient disaster management system today. In this paper we re-shape the requirements and innovative technology are being under the utilization in this field and also perhaps, point out the other sophisticated tools in the IT for better utilization towards incorporated disaster management information system.